Low-dose anti-thymocyte globulin plus low-dose post-transplant cyclophosphamide-based regimen for prevention of graft-versus-host disease after haploidentical peripheral blood stem cell transplants: a large sample, long-term follow-up retrospective study - Li, Xingying; Yang, Jun; Cai, Yu; Huang, Chongmei; Xu, Xiaowei; Qiu, Huiying; Niu, Jiahua; Zhou, Kun; Zhang, Ying; Xia, Xinxin; Wei, Yu; Shen, Chang; et al. (Frontiers in Immunology, 2023)
Introduction The novel low-dose anti-thymocyte (ATG, 5 mg/kg) plus low-dose post-transplant cyclophosphamide (PTCy, 50 mg/kg) (low-dose ATG/PTCy)-based regimen had promising activity for prevention of graft-versus-host disease (GVHD) in haploidentical-peripheral blood stem cell transplantation (haplo-PBSCT), but its impacts on long-term outcomes remain to be defined. Methods We performed a large sample, long-term follow-up retrospective study to evaluate its efficacy for GVHD prophylaxis. Results The study enrolled 260 patients, including 162 with myeloid malignancies and 98 with lymphoid malignancies. The median follow-up time was 27.0 months. For the entire cohort, the cumulative incidences (CIs) of grade II-IV and III-IV acute GVHD (aGVHD) by 180 days were 13.46% (95% CI, 9.64%-17.92%) and 5.77% (95% CI, 3.37%-9.07%); while total and moderate/severe chronic GVHD (cGVHD) by 2 years were 30.97% (95% CI, 25.43%-36.66%) and 18.08% (95% CI, 13.68%-22.98%), respectively. The 2-year overall survival (OS), relapse-free survival (RFS), GVHD-free, relapse-free survival (GRFS), non-relapse mortality (NRM), and CIs of relapse were 60.7% (95% CI, 54.8%-67.10%), 58.1% (95% CI, 52.2%-64.5%), 50.6% (95% CI, 44.8-57.1%), 23.04% (95% CI, 18.06%-28.40%), and 18.09% (95% CI, 14.33%-23.97%, respectively. The 1-year CIs of cytomegalovirus (CMV) and Epstein–Barr virus (EBV) reactivation were 43.46% (95% CI, 37.39%-49.37%) and 18.08% (95% CI, 13.68%-22.98%), respectively. In multivariate analysis, the disease status at transplantation was associated with inferior survivor outcomes for all patients and myeloid and lymphoid malignancies, while cGVHD had superior outcomes for all patients and myeloid malignancies, but not for lymphoid malignancies. Discussion The results demonstrated that the novel regimen could effectively prevent the occurrence of aGVHD in haplo-PBSCT.